Effect of water content on the performance and structure of nanosized TiO2 sol. (27th July 2019) - Yang, Jing; Tian, Li; Li, Bo; Guo, Yingming; Zhang, Yu
Abstract: Titanium dioxide (TiO2 ) sol was prepared using tetrabutyl titanate as a precursor via an acid catalyzed sol–gel process. The influence of water content on the sol density, viscosity, stability and particle size were studied and based on the kinematic viscosity data, Gibbs energies (Δ G *) of activation of the viscous flow was also calculated. Furthermore, the obtained TiO2 materials were characterized by infrared spectroscopy (IR) and X-ray diffraction (XRD) analysis. The results showed that, with the increase of water content, the sol viscosity and zeta potential were increased and the particle size distribution was narrow. When the molar ratio of H2 O/Ti reached 4, the prepared sol was transparent, uniform and stable, and the sol average particle size gets the minimum. Ti–O–Ti bond was the primary structure of TiO2 sol and the formed titanium molecules possessed the line-typed structure. The increase of water content nearly had no obvious influence on the chemical structure of sol. The TiO2 gel material was the amorphous state and it turned into anatase type after calcination at 350° C.